Art, Aesthetics, Justice, and Reconciliation: What can art do?. (2020) - Kerr, Rachel
Abstract : The potential convergence of art and international justice has received greater attention in recent years. In light of recognition of the limitations of international courts and the challenges of outreach, scholars and practitioners have begun to seek alternative ways of fostering engagement among the communities most affected by the crimes under their jurisdiction. In this context, the question has arisen: What can art do? What is the potential role of art and aesthetics in furthering goals of international courts beyond justice, i.e., towards peace and reconciliation? In this essay, I discuss three ways in which art has enormous potential, while also acknowledging that there are associated risks and challenges that might cause us to temper our enthusiasm.